การสร้างโครงสร้างการจำแนกต้นทุนของอุปกรณ์เครื่องกลสำหรับงานโครงการ - นิภาพร สาหล้า (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Miscalculation of fundamental cost estimation found in the mechanical engineering department of the study company was caused by the calculation without correct principal especially human resources cost is insufficient when there is a real construction project. This resulted in an increase of resources to enable project close on time. The objective of this research was to design a more effective fundamental cost estimation system by using Cost Breakdown Structure as a tool to create the fundamental cost estimation system for mechanical equipment. As the Cost Breakdown Structure can identify actual quantity of resources for each working activity, the result is that the fundamental cost estimation is more correct and accurate. The research found that cost calculated by Cost Breakdown Structure was deducted 0.25% from actual period of the construction project but cost calculated by old system higher than actual period is 0.99%. And when compared to the actual period of the construction project, it was found that quantity of man-hour calculated by Cost Breakdown Structure was decreased 22.3% from actual period of the construction project but we found that actual cost of the construction project is higher than cost calculated by old system is 30.64%, as a result the budgeting was uncontrollable. Thus, it can be summarized that the process of cost calculation by Cost Breakdown Structure reflected the actual situation in the organization that a miscalculation by the old system was the cause of assigned task’s quantity not balanced with the limited available resources. The Cost Breakdown Structure is also an important tool for the organization’s management to plan and utilize their available resources the most effectively.